La función del padre en la dinámica relacional de los núcleos monoparentales femeninos (2014)
ABSTRACT: This paper shows the results of a qualitative research approach. It aims to characterize a father’s role in a relationship with a female single parent. This research process was conducted based on theoretical references with a dynamic psychology basis, and founded on psychoanalytic, relational theory. Social risks, as well as an increase in the number of these cases in Colombian households and the need to understand the relational system of these family groups justified this study with semi-structured interviews, and projective tests, which were applied to a sample of 20 couples, (with a pre-existing mother-son relationship). As a result, it was found that within these family groups, the mother enabled the paternal role, thus ensuring the physical and psychological survival of the family through support and its ability to coexist with other people.